2016
DOI: 10.3389/fpsyg.2016.00771
|View full text |Cite
|
Sign up to set email alerts
|

Goodbye or Identify: Detrimental Effects of Downsizing on Identification and Survivor Performance

Abstract: Research shows that after layoffs, employees often report decreased commitment and performance which has been coined the survivor syndrome. However, the mechanisms underlying this effect remain underexplored. The purpose of the paper is to show that reduced organizational identification can serve as an explanation for the survivor syndrome. We conducted a laboratory experiment, in which participants work as a group of employees for another participant who acts as employer. In the course of the experiment, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…One could surmise that this perception might dwindle over time for the remaining, or "surviving" employees, however, the present results indicate that this may not be the case, as employee perception of fair and empowering leadership continues to be low years after the implementation, even for those who are fortunate to keep their job and remain within the company (Vahtera et al, 2004). These results are in line with prior studies showing survivors of downsizing, layoffs, and outsourcing processes to report a lower sense of job security, productivity, organizational attachment, perceived organizational justice and higher turnover intention (Maertz et al, 2010;Drzensky and Heinz, 2015;van Dick et al, 2016).…”
Section: Effects Of Separate Organizational Change On the Work Envirosupporting
confidence: 87%
“…One could surmise that this perception might dwindle over time for the remaining, or "surviving" employees, however, the present results indicate that this may not be the case, as employee perception of fair and empowering leadership continues to be low years after the implementation, even for those who are fortunate to keep their job and remain within the company (Vahtera et al, 2004). These results are in line with prior studies showing survivors of downsizing, layoffs, and outsourcing processes to report a lower sense of job security, productivity, organizational attachment, perceived organizational justice and higher turnover intention (Maertz et al, 2010;Drzensky and Heinz, 2015;van Dick et al, 2016).…”
Section: Effects Of Separate Organizational Change On the Work Envirosupporting
confidence: 87%
“…Finally, we relate informational justice and organizational cynicism to an intention targeted at and reflecting disillusionment with the organization, namely exit intentions. Indeed, previous research suggests that major organizational changes, such as layoffs, can increase the exit intentions of surviving employees (Maertz, Wiley, LeRouge, & Campion, 2010), as described by the so-called survivor syndrome (Van Dick, Drzensky, & Heinz, 2016). Thus, in addition to employee exit being the most dramatic among all possible reactions to cynicism (Hirschman, 1970), exit intentions expressed publicly among co-workers might also lead to perilous and contagious effects among employees (Felps et al, 2009).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…A major reason for the failure of many firms is not just the original causes of the downsizing but also their inability to manage the survivor syndrome afterwards, as survivors are unlikely to behave in the same way after the downsizing, despite the small majority who suffer 'learned helplessness'a condition that explains why sufferers (such as victims of domestic abuse) remain in the same situation, believing little can change and accepting the continued suffering (Appelbaum et al, 1997). van Dick et al (2016) found that identification (the ability of the survivor to identify themselves within the organization immediately after the downsizing) is a mediator of individual performance, so it is imperative to understand the selfcategorization process of individuals that can either plunge the organization into further difficulty or pull it out of existing trouble, which in turn will assist an economy to recover.…”
Section: Introductionmentioning
confidence: 99%